Reconstitution and biochemical characterization of ribonucleoprotein complexes in Type I-E CRISPR-Cas systems - Xiao, Yibei (Methods Enzymol, 2018)
Type I CRISPR-Cas, the most prevalent CRISPR system, features a sequential target searching and degradation process. First, the multi-subunit surveillance complex Cascade recognizes the matching dsDNA target flanked by protospacer adjacent motif (PAM), promotes the heteroduplex formation between CRISPR RNA (crRNA) and the target strand (TS) DNA and displaces the non-target strand (NTS) DNA, resulting in R-loop formation. The helicase-nuclease fusion enzyme Cas3 is then specifically recruited to Cascade/R-loop, nicks and processively degrades the DNA target. Here, by using type I-E CRISPR-Cas system from Thermobifida fusca, we provide protocols for the biochemical reconstitution of the Cascade/R-loop and Cascade/R-loop/Cas3 complexes that allowed for high resolution structure determination and mechanism investigation. The procedures may be applicable for structural and mechanistic investigations of other type I CRISPR-Cas systems, and may serve as a reference for the study of other multi-component protein-nucleic acid complexes.